The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1513/annalsats.201303-052oc
|View full text |Cite
|
Sign up to set email alerts
|

Fever Is Associated with Delayed Ventilator Liberation in Acute Lung Injury

Abstract: Background: Acute lung injury (ALI) is characterized by inflammation, leukocyte activation, neutrophil recruitment, endothelial dysfunction, and epithelial injury, which are all affected by fever. Fever is common in the intensive care unit, but the relationship between fever and outcomes in ALI has not yet been studied. We evaluated the association of temperature dysregulation with time to ventilator liberation, ventilator-free days, and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Similar to our present study, Netzer et al (20) conducted a prospective cohort study on mechanically ventilated patients with acute lung injury. These authors demonstrated that an additional febrile day during the first week after acute lung injury was strongly related to delayed weaning from MV, but more than two thirds of the enrolled cases were related to sepsis.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar to our present study, Netzer et al (20) conducted a prospective cohort study on mechanically ventilated patients with acute lung injury. These authors demonstrated that an additional febrile day during the first week after acute lung injury was strongly related to delayed weaning from MV, but more than two thirds of the enrolled cases were related to sepsis.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, we demonstrated that the degree of body temperature in mechanically ventilated patients was significantly associated with a prolonged TVT. These are the main features of this study that deserve to be highlighted as they differentiate it from the study by Netzer et al (20). …”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This study adds to the literature on temperature abnormalities in critically ill patients with ARDS and is 1 of 2 new studies to investigate the association between temperature and mortality in this subgroup of critically ill patients. Netzer et al 25 recently published findings from their secondary analysis of 450 patients from the Improving Care of Acute Lung Injury patients study cohort. The frequency of temperature alterations in their study was higher than in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Transport limitations coupled with increased interstitial fluid pressure (IFP) within solid tumors [14] disrupt tissue homeostasis and generate hypoxic and necrotic tissue [15], and are also obstacles for systemically administered nanoparticles and chemotherapeutics. While circulating nanoparticles can preferentially exit fenestrated tumor capillaries [16] via the so-called enhanced permeability and retention effect (EPR), their diffusion is hindered beyond 3-5 cell diameters from point of extravasation [17,18].…”
mentioning
confidence: 99%